2015
DOI: 10.1136/jclinpath-2015-203246
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of microRNA analysis to characterisation of pancreatic lesions: a review

Abstract: Pancreatic tumours are usually very aggressive cancer with a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 99 publications
3
14
0
Order By: Relevance
“…In cyst fluid samples, miR-21 and miR-221 were significantly over-expressed in malignant cysts when compared with benign or premalignant [29]. Other miRNAs have been shown to be upregulated or downregulated in plasma, serum, stool and fluids of patients with pancreatic cancer [30,31]. Because these findings are consistent with those reported in pancreatic tissue, the less invasive procedures could be used for early diagnosis especially in patients at high risk to develop PDAC.…”
Section: Mirna and Pancreatic Diseases: Diagnosis Prognosis And Thersupporting
confidence: 71%
See 2 more Smart Citations
“…In cyst fluid samples, miR-21 and miR-221 were significantly over-expressed in malignant cysts when compared with benign or premalignant [29]. Other miRNAs have been shown to be upregulated or downregulated in plasma, serum, stool and fluids of patients with pancreatic cancer [30,31]. Because these findings are consistent with those reported in pancreatic tissue, the less invasive procedures could be used for early diagnosis especially in patients at high risk to develop PDAC.…”
Section: Mirna and Pancreatic Diseases: Diagnosis Prognosis And Thersupporting
confidence: 71%
“…Therapeutic applications for miRNAs consist of two strategies: (1) miRNA replacement therapy against loss of function or (2) anti-miRNA therapy against gain of function [20,31,35]. The replacement therapy has the potential to replace malfunctioning tumor suppressor miRNAs and overcome carcinogenesis by reestablishing their normal levels.…”
Section: Mirna and Pancreatic Diseases: Diagnosis Prognosis And Thermentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of intermediate miR-216/-217 expression in the old P48 +/Cre ;LSL-KRAS G12D mice are not surprising due to the mosaic expression of Kras in these mice. A recent review of the differential miRNA expression in human PDAC tissues compiled an 18 miRNA signature of PDAC from the differentially expressed miRNAs (13 increased and 5 decreased) reported in at least three studies (Visani et al 2015). Our data from miRNA expression profiling in the KRAS G12D transgenic mouse model of PDAC report that 8 of the 18 miRNAs in the human signature were also differentially expressed in the mouse model of PDAC (5 increased and 3 decreased).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous profiling studies over the past decade have shown that the expression miRNAs are altered in cancer, including pancreatic (Bloomston et al 2007, Lee et al 2007, Szafranska et al 2007, Volinia et al 2006). miRNAs reported as deregulated in human PDAC include overexpressed miRNAs (miR-21, miR-155, miR-181a/b, and miR-221/-222) and those with reduced expression in the tumor (miR-217, miR-216a/b, miR-375, and miR-148a) recently reviewed in Visani et al (2015). It was further noted that overexpression of certain miRNAs (i.e., miR-155 or miR-21) (Costinean et al 2006, Medina, Nolde, and Slack 2010) or knockout of other miRNAs such as miR-122 in the liver can contribute to the development of cancer in mice (Hsu et al 2012, Tsai et al 2012).…”
Section: Introductionmentioning
confidence: 99%